Hubungan Pengetahuan Sikap dan Tindakan terhadap Status Gizi - Daning Kurnia Rahmatillah (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2018)
Background: Toddler's nutrition is a serious problem in several areas of Indonesia, one of them is Surabaya. In 2015 Surabaya have 513 toddlers with nutrition status below the red line (BGM). Nutritional status is influenced by nutrition intake of children under five which indirectly can be influenced by several factors include knowledge, attitude and action from mother of toddler.Objective: The aims of this study to determine factors that affect the nutritional status of toddler.Methods: This research is an analytical research with cross sectional design with population of all mother of children aged 1-4 years in RW 15 Wonokusumo Sub district, Semampir Sub district, Surabaya City. The sample of this research is 80 samples with simple sampling random sampling technique.Results: The results of statistical calculations showed there is a relationship between the knowledge with nutritional status of children under five with p = 0.001. Moreover, the result shown there is a relationship between attitude with nutritional status of children with p = 0.001. And also there is a relationship between action with nutritional status of children under five with p = 0. 001.Conclusion: From the results of the analysis that has been done can be concluded that the three variables of knowledge, attitude and action have a significant relationship to the nutritional status of children. It is suggested to Puskesmas to give more education to mother of toddler about what is nutrition status of toddler. For the community is expected to be more active in maintaining nutrient intake for the toddler and for researchers are expected to further examine the analysis of any relationship that can affect the nutritional status of children.ABSTRAKLatar Belakang: Persoalan gizi pada balita masih menjadi permasalahan yang sangat serius pada beberapa daerah di Indonesia salah satunya adalah Kota Surabaya. Pada tahun 2015 di Kota Surabaya terdapat 513 balita dengan status di bawah garis merah (BGM). Status gizi dipengaruhi oleh asupan zat gizi balita yang secara tidak langsung dapat dipengaruhi oleh beberapa faktor meliputi pengetahuan, sikap dan tindakan dari ibu balita.Tujuan: Penelitian ini bertujuan untuk mengetahui faktor apa saja yang dapat mempengaruhi status gizi balita.Metode: Penelitian ini adalah penelitian analitik dengan desain Cross sectional dengan populasi seluruh ibu balita usia 1-4 tahun di wilayah RW 15 Kelurahan Wonokusumo Kecamatan Semampir Kota Surabaya. Sampel penelitian ini didapatkan sebanyak 80 sampel dengan teknik sampling simpel random sampling.Hasil: Hasil perhitungan statistik menunjukkan terdapat hubungan antara pengetahuan dengan status gizi balita dengan p=0,001. Selain itu terdapat pula hubungan antara sikap dengan status gizi balita dengan p=0,001 dan juga terdapat hubungan antara tindakan dengan status gizi balita dengan p=0, 001.Kesimpulan: Dari hasil analisis yang telah dilakukan dapat disimpulkan bahwa ketiga variabel yaitu pengetahuan, sikap dan tindakan memiliki hubungan yang signifikan terhadap status gizi balita. Saran kepada puskesmas agar memberikan edukasi lebih kepada ibu balita tentang apa itu status gizi balita. Bagi masyarakat diharapkan dapat lebih berperan aktif dalam menjaga asupan gizi balitanya serta bagi peneliti diharapkan untuk lebih meneliti analisis hubungan apa saja yang dapat mempengaruhi status gizi balita.